Rosai Dorfman Disease – A case report - Chaudhary, Vinod; Khamkar, Anil; Tiwari, Manish; Suryawanshi, Amol (Indian Journal of Case Reports, 2015)
Rosai Dorfman disease or Sinus histiocytosis with massive lymphadenopathy (SHML) is a benign, self-limiting disorder that commonly presents as massive bilateral and painless cervical lymphadenopathy. We present a case of a 6 year old male child who presented with cervical lymphadenopathy with no other complains and was diagnosed on fine needle aspiration cytology as a case of Rosai Dorfman disease. Patient was given low dose steroids to which patient responded well and became asymptomatic in 15 days.